Evaluation of the apical seal after intraradicular retainer removal with ultrasound or carbide bur Avaliação do selamento apical após remoção de retentor intra-radicular com ultra-som ou instrumento cortante rotatório - Tomie Nakakuki Campos; Cleber Henrique Inoue; Elcio Yamamoto; Ângela Toshie Araki; Lena Katekawa Adachi; Jose Eduardo Chorres Rodriguez (Sociedade Brasileira de Pesquisa Odontológica, 2007)
There are situations in which intraradicular retainers have to be removed and replaced. The objective of this research was to evaluate the apical seal after the removal of a custom cast post and core with a carbide bur or with an ultrasound apparatus. Twenty five roots of extracted human incisors were used. They were endodontically treated and prepared to receive the posts. The posts and cores were cast with 2 types of dental alloys, CuAlZn and PdAg, and were cemented with zinc phosphate cement. After 24 hours, they were removed using the two above mentioned techniques. Then, the roots had their external surface made impermeable by two layers of cyanoacrylate adhesive, leaving only the cervical area for dye penetration. The teeth were immersed in rhodamine for 24 hours. They were then cut and observed under an optical microscope and analyzed with appropriate software (Imagelab). The results were submitted to ANOVA, and they evidenced that, regarding the alloy factor, PdAg posts presented a larger mean infiltration value (2.23 ± 0.48 mm) as compared to the posts made of CuAlZn (1.39 ± 0.48 mm) (p = 0.025). Regarding the technique factor, there was no significant difference (p = 0.9) between the removal of the intraradicular retainer using ultrasound (1.99 ± 0.62 mm) or using a rotating cutting instrument (1.62 ± 0.62 mm). Under these experimental conditions, it was possible to conclude that the degree of apical leakage was directly related to the alloy type, and it was present in both techniques used. Há situações que exigem a remoção ou substituição de retentores intra-radiculares. O objetivo deste trabalho foi avaliar o selamento apical do material obturador após a remoção de pino intra-radicular metálico fundido com instrumento cortante rotatório ou com aparelho de ultra-som. Utilizaram-se 25 raízes de incisivos humanos extraídos, que foram endodonticamente tratadas e preparadas para receberem os pinos. Os retentores intra-radiculares foram fundidos com 2 tipos de ligas odontológicas, CuAlZn e PdAg, e foram cimentados com cimento de fosfato de zinco. Após 24 horas, foram removidos com as 2 técnicas citadas. Em seguida, os dentes foram impermeabilizados com cianoacrilato de etila, permitindo a entrada do corante apenas por via cervical. Os dentes foram imersos em rodamina por 24 horas, depois foram clivados e observados em microscópio óptico de luz e analisados em "software" próprio (Imagelab). Os resultados foram submetidos à análise de variância e mostraram que, para o fator liga, os pinos de PdAg geraram uma média de infiltração maior (2,23 ± 0,48 mm) do que os pinos de CuAlZn (1,39 ± 0,48 mm), com p = 0,025; para o fator técnica, não houve diferença significante, com p = 0,9, entre a remoção com ultra-som (1,99 ± 0,62 mm) e a remoção com instrumento cortante rotatório (1,62 ± 0,62 mm). Nestas condições experimentais, foi possível concluir que o grau de infiltração apical está relacionado com o tipo de liga, e a infiltração esteve presente em ambas as técnicas utilizadas.